The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.heliyon.2021.e08642
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for estimating energy and water consumption patterns in university buildings: case study, Federal University of Roraima (UFRR)

Abstract: Knowing water and energy consumption patterns sets the baseline for understanding their drivers and assessing the performance of potential measures to increase efficiency and/or reliability. These patterns can vary substantially depending on the building characteristics, on the building users and use, on the cultural, social, economic, environmental context in which the building is located, among many other factors. This article presents a general methodological framework for characterizing water and energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
(88 reference statements)
4
6
1
Order By: Relevance
“…The annual total weighted EUIA of all buildings (155 kWh/m 2 ) was obtained in 2021. As for the results of this study in this respect, they are consistent with the results of the studies carried out by Almeida et al [11] in Brazil, Ghenai and Bettayeb [36] in the United Arab Emirates, and Hamida et al [25] in Saudi Arabia, as shown in In addition, here it should be noted that this value is in agreement with the values found in the studies conducted by Hu [9] and Mytafides et al [21] and differs from those reported by Abdo-Allah et al [30] and Chung and Rhee [14], as shown in Table 2. Furthermore, the energy consumption figures concerning laboratories were not compatible, and this is normal as the installed equipment, the operating time, and the EE of the equipment used all differ.…”
Section: Electricity Consumption Indicatorssupporting
confidence: 93%
See 3 more Smart Citations
“…The annual total weighted EUIA of all buildings (155 kWh/m 2 ) was obtained in 2021. As for the results of this study in this respect, they are consistent with the results of the studies carried out by Almeida et al [11] in Brazil, Ghenai and Bettayeb [36] in the United Arab Emirates, and Hamida et al [25] in Saudi Arabia, as shown in In addition, here it should be noted that this value is in agreement with the values found in the studies conducted by Hu [9] and Mytafides et al [21] and differs from those reported by Abdo-Allah et al [30] and Chung and Rhee [14], as shown in Table 2. Furthermore, the energy consumption figures concerning laboratories were not compatible, and this is normal as the installed equipment, the operating time, and the EE of the equipment used all differ.…”
Section: Electricity Consumption Indicatorssupporting
confidence: 93%
“…The annual total weighted EUI A of all buildings (155 kWh/m 2 ) was obtained in 2021. As for the results of this study in this respect, they are consistent with the results of the studies carried out by Almeida et al [11] in Brazil, Ghenai and Bettayeb [36] in the United Arab Emirates, and Hamida et al [25] in Saudi Arabia, as shown in Table 2, and that may be because the values of CDD are close due to convergent climate conditions. When comparing the results of this study with those of other studies concerning classrooms, for example, we notice that in this study, annual consumption in this respect totals 172 kWh/m 2 , whereas in other studies, figures range between 29 and 145 kWh/m 2 .…”
Section: Electricity Consumption Indicatorssupporting
confidence: 92%
See 2 more Smart Citations
“…However, without doing a detailed energy audit, some researchers use targeted surveys to collect the necessary data for regression analyses. For instance, Almeida et al [25] proposed a methodology for estimating the water and energy consumption in university buildings while Nematchoua et al [26] designed a questionnaire to collect energy consumption data in different types of buildings (residential and commercial) in 12 cities in Madagascar. Furthermore, Ma et al [27] collected energy consumption data from on-site surveys of 17 schools in Tianjin, China and found that a variety of energy sources such as electricity, natural gas, municipal heating, coal, gasoline, diesel oil, tap water, reclaimed water, and alcohol-based fuels were consumed by the 17 schools, while 15 states in Brazil joined a survey to provide necessary data from 5321 schools that were used to build a regression model for annual energy consumption [28].…”
Section: Introductionmentioning
confidence: 99%